2010
DOI: 10.1016/j.neuroscience.2009.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine and extinction of fear conditioning

Abstract: Introduction-Despite known health risks, nicotine use remains high, especially in populations diagnosed with mental illnesses, including anxiety disorders and Post-Traumatic Stress Disorder (PTSD). Smoking in these populations may relate to the effects of nicotine on emotional memories. The current study examined the effects of nicotine administration on the extinction of conditioned fear memories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 46 publications
3
38
2
1
Order By: Relevance
“…Therefore, according to some accounts, PTSD may be attributed to impaired safety learning (Davis, Falls, & Gewirtz, 2000; Lissek et al, 2005). The effects of nicotine exposure on safety learning and extinction have been investigated using the animal models of fear extinction and contextual safety discrimination (Elias, Gulick, Wilkinson, & Gould, 2010; Kutlu & Gould, 2014; Kutlu, Oliver, & Gould, 2014; Tian et al, 2008). For example, Elias et al (2010) found that acute nicotine enhanced extinction and impaired renewal of cued fear memories when administered during the extinction phase, whereas nicotine administration during both training and extinction phases impaired extinction and enhanced renewal of cued fear.…”
Section: Involvement Of Nachrs In Anxiety and Anxiety Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, according to some accounts, PTSD may be attributed to impaired safety learning (Davis, Falls, & Gewirtz, 2000; Lissek et al, 2005). The effects of nicotine exposure on safety learning and extinction have been investigated using the animal models of fear extinction and contextual safety discrimination (Elias, Gulick, Wilkinson, & Gould, 2010; Kutlu & Gould, 2014; Kutlu, Oliver, & Gould, 2014; Tian et al, 2008). For example, Elias et al (2010) found that acute nicotine enhanced extinction and impaired renewal of cued fear memories when administered during the extinction phase, whereas nicotine administration during both training and extinction phases impaired extinction and enhanced renewal of cued fear.…”
Section: Involvement Of Nachrs In Anxiety and Anxiety Disordersmentioning
confidence: 99%
“…The effects of nicotine exposure on safety learning and extinction have been investigated using the animal models of fear extinction and contextual safety discrimination (Elias, Gulick, Wilkinson, & Gould, 2010; Kutlu & Gould, 2014; Kutlu, Oliver, & Gould, 2014; Tian et al, 2008). For example, Elias et al (2010) found that acute nicotine enhanced extinction and impaired renewal of cued fear memories when administered during the extinction phase, whereas nicotine administration during both training and extinction phases impaired extinction and enhanced renewal of cued fear. This suggests that acute nicotine may enhance recovery and extinction of cued fear conditioning by potentially strengthening encoding and facilitating new inhibitory learning during acquisition and extinction, respectively.…”
Section: Involvement Of Nachrs In Anxiety and Anxiety Disordersmentioning
confidence: 99%
“…However, it should be noted that higher doses of nicotine are anxiogenic and can act as stressors (Yu & Sharp, 2010). Interestingly, nicotine can also enhance cued extinction after delay fear conditioning (Elias, Gulick, Wilkinson, & Gould, 2010), a task that relies on cortical substrates similar to those that support the acquisition of trace fear conditioning (Stafford, Raybuck, Ryabinin, & Lattal, 2012). …”
Section: Nicotine and Fear Conditioningmentioning
confidence: 99%
“…Previous work does suggest that nicotine can function as a cognitive enhancer, augmenting learning, memory, and attention (Couey et al, 2007; Levin et al, 2006; Mansvelder et al, 2006; Newhouse et al, 2004) with effects demonstrated in extinction (Elias et al, 2010; Kaplan et al, 2011). As extinction is new learning (Bouton and King, 1983, Rescorla, 2004), the nicotine treatment may be enhancing this learning.…”
Section: Discussionmentioning
confidence: 99%
“…As extinction is new learning (Bouton and King, 1983, Rescorla, 2004), the nicotine treatment may be enhancing this learning. This explanation does have a major issue; the enhancement of learning associated with nicotine is found when nicotine is administered concurrently with the learning (Elias et al, 2010; Gould and Higgins, 2003; Gould and Wehner, 1999; Tian et al, 2008). In the present report, nicotine was administered during the self-administration phase and halted prior to the extinction phase.…”
Section: Discussionmentioning
confidence: 99%